Penerapan Copywriting Untuk Optimalisasi Digital Marketing Bagi Guru SMK Kridawisata Bandar Lampung - Permatasari, Berlintina; Jaelani, Jaelani; Suprayogi, Suprayogi; Camelia, Camelia (Society : Jurnal Pengabdian Masyarakat, 2023)
One of the successful points of digital marketers is their ability to maximize product and service promotion techniques using digital distribution channels such as websites, ad words, email, and various other social networks. Tourism vocational high school graduates are expected to be successful in the business world where they must be equipped with good marketing skills. Considering the importance of a marketer having copywriting skills, copywriting training is needed for them. The method used is the ABCD approach where the asset in this community is the SMK Kridawisata Bandar Lampung students who have started entrepreneurship. This activity was carried out directly in the form of basic marketing theory and ad copywriting training for the teacher of the school so that they can introduce digital marketing to their students. This training activity was carried out at SMK Kridawisata Bandar Lampung. The results of the activity show that there has been an increase in language and copywriting skills from each participant, where the most mastered skill on average is writing AIDA.